TEACHERS’ PERCEPTION OF CHALLENGES IN THE IMPLEMENTATION OF ENGLISH DAY PROGRAM: IMPLICATION FOR IMPROVING STUDENTS’ SPEAKING SKILLS AND SELF-EFFICACY - Mahmudah, Nur; Saehu, Andang; Puspitasari, Maya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore teachers' perceptions of the challenges in implementing the English Day program at MAN 1 Kota Pekalongan and identify its implications for the students’ speaking skills and self-efficacy. The English Day program is designed to increase the use of English in the school environment, but it faces various barriers, both from the student's and teachers' side. The research method used was qualitative with a case study design, involving in-depth interviews, participatory observation, and documentation. The research participants comprised three English teachers and ten grade XI students directly involved in the program. The results show that the main challenges in implementing the program include low student motivation and confidence, limited teacher competence in English, and lack of adequate supporting facilities. Nevertheless, the program has the potential to improve students' speaking skills if supported by training for teachers and strengthening learning facilities. This research provides important implications for the development of English Day programs in other schools, with recommendations to improve teacher competence and create a more supportive learning environment for students to practice English. Keywords: Teachers' perceptions, challenges, English Day program, speaking skills, students' self-efficacy.